1998
DOI: 10.1038/bjc.1998.135
|View full text |Cite
|
Sign up to set email alerts
|

The use of videotaped information in cancer genetic counselling: a randomized evaluation study

Abstract: Summary A video of introductory information about inherited susceptibility to breast cancer was made in consultation with clinicians in four Scottish cancer family clinics. One hundred and twenty-eight women, newly referred for breast cancer risk counselling were randomized to receive the video before (n = 66) or after (n = 62) counselling. Data were collected before randomization at clinic and by postal follow-up at 1 month. The Video Before group had shorter consultations with the breast surgeon (mean = 1 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
102
1
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(112 citation statements)
references
References 10 publications
7
102
1
2
Order By: Relevance
“…The DA had no negative impact on a broad range of well-being outcomes, and did not deter women from receiving their test result, while it improved understanding of the treatment options and consequences. Similar results on the use of a video in BRCA1/2 counselling have been reported (Cull et al, 1998). Their video, however, was more general and introductory and less focused on the treatment decision.…”
Section: Discussionsupporting
confidence: 76%
“…The DA had no negative impact on a broad range of well-being outcomes, and did not deter women from receiving their test result, while it improved understanding of the treatment options and consequences. Similar results on the use of a video in BRCA1/2 counselling have been reported (Cull et al, 1998). Their video, however, was more general and introductory and less focused on the treatment decision.…”
Section: Discussionsupporting
confidence: 76%
“…After genetic counselling, small reductions in anxiety levels were seen in all groups. Even though the participants' baseline mean anxiety scores were slightly higher than the norm for adult women (score of 35), they were comparable to anxiety levels found in other studies that have used the STAI (Cull et al, 1998;Cull et al, 1999;Julian-Reynier et al, 1999;Brain et al, 2000). The between-trial differences support the decision to conduct two parallel trials rather than multicentre trial, where the data would have been pooled (Bowling, 1997).…”
Section: Discussionsupporting
confidence: 61%
“…We do not have access to data on how many of the participants actually went ahead with genetic testing, or their actual test results. The primary outcome measure was anxiety, the reduction of which is regarded as a key counselling objective (Shaw et al, 1999;Brain et al, 2000;Meiser and Halliday, 2002) and a number of evaluations of genetic counselling for familial cancer have identified the pre-and postcounselling assessment of generalised anxiety as a main outcome measure (Cull et al, 1998Julian-Reynier et al, 1999;Brain et al, 2000;Kent et al, 2000;Bish et al, 2002;Bowen et al, 2004). Evidence from systematic reviews suggests that, overall, genetic counselling has the effect of significantly reducing patients' anxiety levels, at least in the short-term (Meiser and Halliday, 2002;Butow et al, 2003;Braithwaite et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Studies that have examined levels of breast cancer genetics knowledge among women with a family history of breast cancer (Lerman et al, 1996Hughes et al, 1997;Wonderlick and Fine, 1997;Cull et al, 1998;Bluman et al, 1999;Donovan and Tucker, 2000) have found wide variation in knowledge about many facets of genetic testing, including the cancer risks associated with different genes and different mutations and the effectiveness of interventions, for example screening, chemoprevention, or surgery for reducing risk (Geller et al, 1997;Audrain et al, 1998;Bluman et al, 1999).…”
mentioning
confidence: 99%